2021
DOI: 10.11604/pamj.2021.39.159.28282
|View full text |Cite
|
Sign up to set email alerts
|

Impact de la pandémie de la COVID-19 sur l´utilisation des services de santé dans la ville de Niamey: une analyse dans 17 formations sanitaires de janvier à juin 2020

Abstract: Le défi que pose la pandémie de la COVID-19 sur le système de santé en Afrique est énorme mais pas bien quantifié en ce jour. Nous avons évalué les conséquences de la COVID-19 sur les activités curatives et préventives des formations sanitaires sur une période de six mois au niveau de 17 centres de sante intégré au Niamey de manière en comparant la première moitié de l´année 2020 à celle de l´année 2019. Les différences furent plus prononcées au deuxième trimestre 2020, avec une réduction de 34% (95%IC: -47% à… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 7 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…( 9 ) Another study in Yemen reported a 10% reduction in surgery and a 4% decrease in medical consultation during the early phase of the pandemic in 2020 ( 16 ). Similar trends were observed in other countries, such as Armenia ( 17 ), Iran ( 18 ), and Italy ( 19 ). However, the magnitude and duration of the declines varied across countries and healthcare sectors, reflecting differences in the pandemic’s severity, public health response, healthcare system capacity, and patient behavior.…”
Section: Discussionsupporting
confidence: 82%
“…( 9 ) Another study in Yemen reported a 10% reduction in surgery and a 4% decrease in medical consultation during the early phase of the pandemic in 2020 ( 16 ). Similar trends were observed in other countries, such as Armenia ( 17 ), Iran ( 18 ), and Italy ( 19 ). However, the magnitude and duration of the declines varied across countries and healthcare sectors, reflecting differences in the pandemic’s severity, public health response, healthcare system capacity, and patient behavior.…”
Section: Discussionsupporting
confidence: 82%
“…This phenomenon has also been observed elsewhere, in Côte d’Ivoire notably where almost 70% of people said that their daily expenditure had risen because of preventive measures [ 36 ]. It was also observed in 17 health facilities in Niamey in Niger, where the COVID-19 pandemic had negative effects on the service provision to the most vulnerable groups, such as women and children [ 42 ]. Similarly in Nigeria and Ethiopia where 21.8% and 19.3% of members of the community said that family members and themselves had difficulty gaining access to child healthcare services, maternal healthcare services and other healthcare services, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Niamey, the capital of neighboring Niger, a study on 17 different health centers also found a reduction between 29% and 58%. 24 …”
Section: Discussionmentioning
confidence: 99%